2013
DOI: 10.1039/c3ee40878g
|View full text |Cite
|
Sign up to set email alerts
|

A green Li–organic battery working as a fuel cell in case of emergency

Abstract: The routine access to electricity always means a drastic change in terms of quality of life making it easier and safer. Consequently, the global electric demand both on and off-the-grid is growing and calls for ongoing innovation to promote reliable, clean and safe power supplies. In this context, the development of new chemistries for batteries and fuel cells could play a critical role. From our prospects aiming at fostering the concept of sustainable organic batteries, we report in this article on the peculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
128
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(137 citation statements)
references
References 46 publications
7
128
2
Order By: Relevance
“…137,140 Note that other "green" positive electrode materials have been proposed such as ellagic acid ( Figure 6.8(g)) or the redox cofactor riboflavin (Figure 6.8(h)) but their oxidized state (nonlithiated compound) prohibits a possible use in Li-ion cell. As previously explained, 137,140,193 the presence of permanent negative charges in the vicinity of redox active carbonyls in both oxidized and reduced states enables a quite good stability toward aprotic liquid electrolyte (no dissolution) but also a shift toward lower potential values as compared to carboxylic acids. Such structures that belong this time to inverse W€ urster-type redox systems, 141 react typically at lower potential in comparison with quinonic-type structures previously reported (i.e., in the range of 0.6e1.6 V vs Li þ /Li 0 ).…”
Section: Particular Case Of the Redox-active C ¼ O Moietymentioning
confidence: 84%
See 2 more Smart Citations
“…137,140 Note that other "green" positive electrode materials have been proposed such as ellagic acid ( Figure 6.8(g)) or the redox cofactor riboflavin (Figure 6.8(h)) but their oxidized state (nonlithiated compound) prohibits a possible use in Li-ion cell. As previously explained, 137,140,193 the presence of permanent negative charges in the vicinity of redox active carbonyls in both oxidized and reduced states enables a quite good stability toward aprotic liquid electrolyte (no dissolution) but also a shift toward lower potential values as compared to carboxylic acids. Such structures that belong this time to inverse W€ urster-type redox systems, 141 react typically at lower potential in comparison with quinonic-type structures previously reported (i.e., in the range of 0.6e1.6 V vs Li þ /Li 0 ).…”
Section: Particular Case Of the Redox-active C ¼ O Moietymentioning
confidence: 84%
“…This situation being highly detrimental to the development of high-energy density organic batteries, Poizot and coworkers have pointed out the interest of using redox-active structures bearing permanent negative charges (anionic backbone) to overcome this unwanted dissolution. 181 However, the output voltage was limited to an average value of w1 V. More recently, the successful synthesis of dilithium (2,5-dilithium-oxy)-terephthalate (namely Li 4 -p-DHT or Li 4 DHTPA, Figure 6.8(f)) first reported by Renault et al,193 enables the achievement of another symmetric and all-organic LiB working at an average voltage of 1.8 V (130 Wh/kg) 194 thanks to a peculiar dual and antagonist redox-activity. The first attempt was reported in 2009 through the use of tetralithium salt of tetrahydroxybenzoquinone (Li 4 C 6 O 6 , Figure 6.8(e)), an amphoteric redox compound able to cycle between Li 2 C 6 O 6 and Li 6 C 6 O 6 .…”
Section: Particular Case Of the Redox-active C ¼ O Moietymentioning
confidence: 99%
See 1 more Smart Citation
“…[90] As an example, NTCDA could realize approximately 18-Li uptake with a cut-off voltage of 0.001 V (vs Li + /Li), giving a high capacity of ≈1800 mAh g -1 (Figure 4a). Generally, both low crystalline [94] and nanostructures [38,95,96] increase the utilization of carbonyls. Recently, Lee et al found that nonfused aromatic compounds also showed superlithiation.…”
Section: Capacity-orientedmentioning
confidence: 99%
“…For example, one of the earliest attempts was through the synthesis of lithium salts [8,9,[13][14][15], which delivered relatively better cycling stability and specific capacity compared with the previously reported small molecules. It was reported that Li 2 C 8 H 4 O 4 (Li terephthalate) could accept two lithium ions to give an initial reversible capacity of 300 mAh g −1 at 1 C [9].…”
mentioning
confidence: 99%